Contribution of Age, V02 Max, and Confidence to the Achievement of Athletes in Karo Regency in North Sumatra - Agung Sunarno (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to determine the contribution of Age, V02 Max, and Confidence to the Achievement of Tanah Karo Athletes in the Province of North Sumatra, Indonesia. Descriptive research method with correlational techniques. The sample is 18 athletes. The instruments used are documentation, tests and measurements as well as questionnaires. The data analysis technique used regression analysis. The results showed that: (1) Age contributed 82.7%, (2) V02max contributed 38.6%, (3) Self-confidence contributed 60.5% and (4) Age, Vo2 Max and Self-confidence overall together contributed 84.2% to the achievement. Conclusion Age, Vo2 Max and Self Confidence make a positive contribution to the achievements of Tanah Karo athletes, North Sumatra Province, Indonesia.